2018
DOI: 10.1111/poms.12808
|View full text |Cite
|
Sign up to set email alerts
|

The Boarding Patient: Effects of ICU and Hospital Occupancy Surges on Patient Flow

Abstract: Patients admitted to a hospital’s intensive care unit (ICU) often endure prolonged boarding within the ICU following receipt of care, unnecessarily occupying a critical care bed, and thereby delaying admission for other incoming patients due to bed shortage. Using patient-level data over two years at two major academic medical centers, we estimate the impact of ICU and ward occupancy levels on ICU length of stay (LOS), and test whether simultaneous “surge occupancy” in both areas impacts overall ICU length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Apart from the interest in avoiding excess mortality that comes with refusal of ICU admittance [ 16 ], availability is expected for the next critically ill patient in need of specialized care. Efficient use of resources in such a tertiary ICU does not allow final mobilization or boarding of patients who can be cared for in other ICUs [ 17 ]. Indeed, patients not in need of tertiary care are not necessarily kept for longer time in our CICU.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the interest in avoiding excess mortality that comes with refusal of ICU admittance [ 16 ], availability is expected for the next critically ill patient in need of specialized care. Efficient use of resources in such a tertiary ICU does not allow final mobilization or boarding of patients who can be cared for in other ICUs [ 17 ]. Indeed, patients not in need of tertiary care are not necessarily kept for longer time in our CICU.…”
Section: Discussionmentioning
confidence: 99%
“…Due to large number of comparisons for multiple factors, we only report the single factor results, shown in Table 9. For the multiple factors and interaction terms, we found that interactions of p:w, p:d, w:d, and p:w:d contained 48 120 , 57 66 , 48 66 , and 820 1128 significantly different means, respectively. Table 10 presents a summary of the results obtained by averaging across all four patient mix combinations, for discharge windows and wait thresholds.…”
Section: Discussionmentioning
confidence: 90%
“…An empirical study of similar chain of incidences was carried out by Long and Mathews. 48 They also suggested prioritizing ICU patients for discharge when floor occupancy exceeds a certain threshold, for example, 80%. In fact, patients who complete their ICU service during the day shift (from 7:00 to 19:00), experience significant discharge delays due to bed shortage in downstream units.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(D) Workload smoothing: Completing the discharge of customers whose processing is complete earlier, in anticipation of incoming demand. Long & Mathews (2017) observed that ICU patients often board while awaiting transfer to other hospital units. By decomposing ICU LOS into care time and boarding time, they found that the shorter LOS during higher ICU occupancy is not related to early discharge decisions (in contrast to findings by other researchers about early discharge, which we cited under the task reduction mechanism) but is instead caused by decreased boarding times of patients that are discharged in order to free ICU capacity.…”
Section: Server-load Mechanismsmentioning
confidence: 99%